Primerjava učinkovitosti vadbe za izboljšanje moči mišic in ravnotežja trupa med vadbo na napravi 3d Newton in fizioterapevtskimi vajami za stabilizacijo trupa pri dekletih z adolescentno idiopatsko skoliozo - Udovčić Pertot, Anja (Rehabilitacija (Ljubljana), 2017)
Background: 3D Newton is a hi-tech device made for strengthening trunk muscles and balance. It is intended for patients with different diagnoses, including scoliosis. With a small pilot study, we wanted to compare the effectiveness of training on 3D Newton with the effectiveness of a specific physiotherapeutic program that is based on three-dimensional self-correction and trunk stabilisation in improved posture. Methods: We included eight girls (aged from 12 to 16 years), who were randomly assigned to one of two groups: the first group exercised on 3D Newton and the second group exercise within a specific physiotherapeutic program. We tested all the girls before and after the exercise program on 3D Newton to assess balance (proprioception, test A) and trunk muscle strength (test B). All the girls attended exercise program twice a week for five weeks. Results: In six out of the eight girls we observed improvement on both tests, but the improvement was not statistically significant in either group (Group 1 % test A: p=0.534, test B: p=0.158; Group 2 % test A: p=0.437, test B: p=0.082). There was also no statistically significant difference in mean progress between the groups (test A: p=0.721, test B: p=0.800). Conclusion: Exercise on the expensive 3D Newton device does not improve the postural balance significantly more than the specific exercise program, so its use in children with scoliosis is not justifiable.
Keywords: Adolescent; Exercise Therapy; mišična moč; muscle strength; postural balance; propriocepcija; proprioception; Scoliosis; skolioza; telesno ravnotežje; trunk; trup